Cu(II), Ni(II), Co(II), and Mn(II) Complexes of Arylidenes-2-Amino-4-Methyl Pyrimidine - Gad, A.A.; Gabr, A.A.; El-Taher, M.A. (Asian Journal of Chemistry, 2010)
A number of chelate complexes of Cu(II). Ni(II), Co(II) and Mn(II) with some heterocyclic Schiff bases derived froin 2-amino-4-methyl pyrimidine and salicylaldehyde (L1), p-hydroxy benzaldehyde (L2) and vanillin (L3) have been prepared. The stoichiometry and the structure of the complexes were studied using elemental analysis, conductivity measurements, electronic and i.r. spectra.